Room temperature second sound in cumulene. Issue 28 (9th July 2021) - Melis, Claudio; Fugallo, Giorgia; Colombo, Luciano
Abstract : Second sound is a thermal regime occurring in a wave-like fashion, usually observed at cryogenic temperatures. By atomistic simulations we provide evidence that it might as well occur in a carbon chain even at room temperature. Abstract : Second sound is known as the thermal transport regime occurring in a wave-like fashion, usually identified in a limited number of materials only at cryogenic temperatures. Here we show that second sound in a μm-long carbon chain (cumulene) might occur even at room temperature. To this aim, we calibrate a many-body force field on the first principles calculated phonon dispersion relations of cumulene and, through molecular dynamics, we mimic laser-induced transient thermal grating experiments. We provide evidence that by tuning temperature as well as the space modulation of its initial profile we can reversibly drive the system from a wave-like to a diffusive-like thermal transport. By following three different theoretical methodologies (molecular dynamics, the Maxwell–Cattaneo–Vernotte equation, and heat transport microscopic theory) we estimate for cumulene a second sound velocity in the range of 2.4–3.2 km s −1 .